The Concept of Justice in Islam According to Majid Khadduri - Sangkot Sirait (IJISH (International Journal of Islamic Studies and Humanities), 2022)
This paper aims to describe the concept of justice in Islam according to Majid Khadduri, a Muslim scholar in the modern era. In Islamic theology, for example, justice is not only related to aspects of humanity but also divinity. In the secular sciences, justice is widely discussed in terms of substance and procedure. Likewise, in the discourse of Islamic theology, the value in question tends only to divinity, meaning that the measure of good value is God or the texts of the holy book. However, for Majid Khadduri, these values are not only related to humanity but at the same time they must be close to what God wants and religion in general. The synthesis of the two views above seems to be united in the concept of Khadduri. Therefore, the problem in this paper is how the construction of justice according to Majid Khadduri and its implications for the formulation of justice in the context of religious humanity. The results of the study show that human actions are judged fairly if they are based on correct norms and carried out with good procedures. In addition, with the development of social problems in society, such as injustice, it is also important to formulate the concept of justice which truly is a concept that can provide and be useful in solving this sense of injustice. This article will contribute and can be used as an approach in creating the spirit of changing, enlightening in Muslim society.